2020
DOI: 10.1177/2049936120978095
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial co-infections and antibiotic prescribing practice in adults with COVID-19: experience from a single hospital cluster

Abstract: Background: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected millions of individuals since December 2019, resulting in significant morbidity and mortality globally. During the 1918 Influenza Pandemic, it was observed that influenza was associated with bacterial co-infections. However, empirical or prophylactic antibiotic use during viral pandemics should be balanced against the associated adverse drug events. Methods: In this retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 39 publications
0
39
0
2
Order By: Relevance
“…Since antagonistic TLR and NLR interactions tend to be initiated over time measured by many hours or several days (see Section 2.3), Figure 8 may well explain how the cytokine storm in severe COVID-19 is initiated and Figure 3A the status of the innate system as it attempts to moderate its cytokine production. One final complication is that many severe COVID-19 patients are treated with multiple antibiotics [201][202][203][204][205][206][207][208][209][210][211][212], which may further modify the expression of bacterially activated TLR and NOD1/NOD2.…”
Section: Do Combinations Of Viruses and Bacteria Explain Innate Recepmentioning
confidence: 99%
“…Since antagonistic TLR and NLR interactions tend to be initiated over time measured by many hours or several days (see Section 2.3), Figure 8 may well explain how the cytokine storm in severe COVID-19 is initiated and Figure 3A the status of the innate system as it attempts to moderate its cytokine production. One final complication is that many severe COVID-19 patients are treated with multiple antibiotics [201][202][203][204][205][206][207][208][209][210][211][212], which may further modify the expression of bacterially activated TLR and NOD1/NOD2.…”
Section: Do Combinations Of Viruses and Bacteria Explain Innate Recepmentioning
confidence: 99%
“…Empiric, potent, or prolonged antibiotic therapy increases risk for nosocomial infection. In addition, the COVID-19 context has been significantly associated with increasing antibiotic use [119][120][121]. The presence of a potentially complex infection along with the use of either steroids or immunomodulatory treatments otherwise increases the potential for secondary bacterial infections.…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%
“…The COVID-19 experience on this theme is considerable to date. Empiric antibiotic use is common among these patients [76,[119][120][121]131]. The frequency of such use may decline with experience [76].…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it has been observed that a significant proportion of antimicrobial was prescribed imprudently where microbial or bacterial infection possibility were improbable 53 . Multivariate analysis revealed that at the hospital's point of admission, pneumonic changes in chest radiograph were suggestive of bacterial co-infection among the COVID-19 patients and demands prudent use of antimicrobials 54 . Similarly, multiple research studies revealed that only those COVID-19 patients with radiologically identified bilateral pulmonary infection required antimicrobials therapy [55][56][57][58][59][60] .…”
Section: " Sir Alexander Flemingmentioning
confidence: 99%